Development of Adhesive Materials from Polystyrene Foam Waste - Mualim, Ahmad Dzaky; Roziafanto, Achmad Nandang; Sabarno, Abiyyu Adistya Wahid; Khoirurrizal, Muhammad Fadhil; Alfiani, Putri; Maryam, Saffana; Putri, Yasinta Rahmatul (Indonesian Journal of Chemical Studies, 2024)
Polystyrene is a type of plastic that is difficult to decompose naturally, leading to waste that contributes to environmental pollution. This study developed adhesive materials based on polystyrene waste to reduce environmental impacts while addressing the need for eco-friendly adhesives. The adhesives were prepared by dissolving polystyrene foam waste in gasoline and acetone with various compositions. The solvents with a composition ratio of gasoline and acetone of 100:0; 90:10; 80:20; 70:30; 60:40; and 50:50 were coded as A, B, C, D, E, and F. Tests were carried out to determine the solubility of polystyrene foam in various solvent compositions and the mechanical properties of samples, including shear force, shear strength, and strain (elongation). Paper, cardboard, and wood were used as gluing materials. The adhesive strength was also compared with that of commercial adhesives. The adhesive samples were then characterized using Fourier-Transform Infrared Spectroscopy (FTIR). The shear strength results obtained for samples code A, B, C, D, E, and F were 119.95 kPa, 103.68 kPa, 96.64 kPa, 124.56 kPa, 150.08 kPa, and 157.80 kPa, respectively. The findings showed that the adhesive sample coded F synthesized using a solvent composition of 50: 50 gasoline: acetone exhibited superior adhesive ability than other variations. This sample can potentially serve as a substitute for commercial adhesives that are suitable for bonding various materials.